Labour Economics - From the Technological Development Perspective - Boros, József (International Journal of Engineering and Management Sciences, 2024)
The impact of technological advancements on the labor market and innovation processes is a critically important research area. The aim of this study is to examine the emergence and frequency of technological innovations in scientific publications, with a particular focus on the Journal of Labour Economics from 2000 to 2020. The research employs content analysis methods, searching for eight different terms and expressions related to technological development (e.g., technology, artificial intelligence, machine learning) across 1405 articles. The study also analyzes the number of occurrences and annual publication trends of these terms. A total of 9469 instances were identified, indicating that in 64,7% of the cases, at least one technological term appeared. An analysis of annual trends reveals an increase in the usage of certain keywords (technology, artificial intelligence, and machine learning). In a smaller subset of articles, only 1%, technological terms were mentioned at least 50 times. The results suggest that although the topic of technological development plays a significant role in labor market research, the frequency of its appearance and the depth of analysis vary considerably. The increase in the appearance of technological terms is predominantly observed in the fields of artificial intelligence and machine learning. These findings are specific to a single journal, indicating the need for further research involving other labor market journals to ensure representativeness.